The Application of Blended Learning’s Station Rotation Method in Elementary School’s Science Education to Improve Higher Order Thinking Skills - S Christina; Rusijono Rusijono; B Bachtiar (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This study applied Station rotation as one of differentiated instructions. Each student who comes in the classroom has a unique characteristic to capture the lesson in the classroom. Blended Learning’s Station Rotation is a learning method that nurtures higher order thinking skills and is able to meet all the students learning needs. This study is a classroom action research and uses One-Group Pretest-Posttest Design with descriptive quantitative analysis techniques. Data is collected through observation, interviews, teacher’s journal, and students’ learning outcomes. Station rotation is able to promote students’ performance in problem solving, critical thinking, and finishing project creatively to apply their understanding in their learning process. The result showed, the Station Rotation method promotes higher order thinking skills.